2014
DOI: 10.1016/j.jval.2014.08.1918
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Virtual Reality Exposure Therapy in the Management of Symptoms Associated With Post Traumatic Stress Disorder

Abstract: the Total SGRQ score (r= 0.73) and Symptoms (r= 0.62); Activity (r= 0.55), Impact (r= 0.72) subscales; the modified MRC Dyspnoea scale (r= 0.54), FACIT-F (r= -0.66); HADS Anxiety (r= 0.53) and Depression (r= 0.54). The MEMSI also demonstrated good overall fit to the Rasch model (Chi-squared 26.6; df 20; p= 0.26) and distribution of item scores. ConClusions: The final MEMSI contains 10-item and is a reliable, valid, unidimensional self-reported outcome measure of early morning symptoms for people with COPD. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Another study reported that the VR was very effective in managing post-traumatic stress disorder (Jiandani et al, 2014). The present study supports the earlier studies as there was a signi icant decrease in the anxiety scores followed by the VR.…”
Section: Resultssupporting
confidence: 90%
“…Another study reported that the VR was very effective in managing post-traumatic stress disorder (Jiandani et al, 2014). The present study supports the earlier studies as there was a signi icant decrease in the anxiety scores followed by the VR.…”
Section: Resultssupporting
confidence: 90%
“…The use of VR has been adopted in a variety of therapeutic ways such as physical rehabilitation in neurological diseases, rehabilitation for various psychiatric illnesses and postcancer rehabilitation in breast cancer survivors. [10][11][12][13][14] Our subject of interest is the application of VR technology in the field of cardiac rehabilitation. It has been used during both aerobic exercises and relaxation exercises separately.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%